Tabernaemontana divaricata extract inhibits neuronal acetylcholinesterase activity in rats - Chattipakorn S. (2014)
The current pharmacotherapy for Alzheimer's disease (AD) is the use of acetylcholinesterase inhibitors (AChE-Is). A previous in vitro study showed that Tabernaemontana divaricata extract (TDE) can inhibit AChE activity. However, neither the AChE inhibitory effects nor the effect on neuronal activity of TDE has been investigated in vivo. To determine those effects of TDE in animal models, the Ellman's colorimetric method was implemented to investigate the cortical and circulating cholinesterase (ChE) activity, and Fos expression was used to determine the neuronal activity in the cerebral cortex, following acute administration of TDE with various doses (250, 500 and 1000 mg/kg) and at different time points. All doses of TDE 2 h after a single administration significantly inhibited cortical AChE activity and enhanced neuronal activity in the cerebral cortex. The enhancement of Fos expression and AChE inhibitory effects in the cerebral cortex among the three TDE-treated groups was not significantly different. A 2 h interval following all doses of TDE administration had no effect on circulating ChE activity. However, TDE significantly inhibited circulating AChE 10, 30 and 60 min after administration. Our findings suggest that TDE is a reversible AChE-I and could be beneficial as a novel therapeutic agent for AD. © 2006 Elsevier Ireland Ltd. All rights reserved.